Improving student engagement in higher education through Mobile-Based Interactive Teaching Model using Socrative - Lim, Woan Ning * (2017)
One of the main problem in higher education teaching is low students’ levels of engagement leading to poor learning performance. Broad teaching strategies, methods and tools are developed over the years to address this concern. In recent years, with the increasing numbers of students accessing the internet using mobile devices, there has been growing interest in embracing the mobile technology in teaching to improve the student participation in the classroom. This research describes the design and implementation of a mobile-based interactive teaching model with in-class and off-class components aided by Socrative online audience response system to improve students’ engagement in a private university in Malaysia. A total of 45 students from undergraduate computing course had participated in this experimental study. The activities such as polls, exercises, quizzes and games was used to stimulate the discussion and encourage two ways communication between instructor and students. Both qualitative and quantitative data comprises of students’ feedbacks, academic results, attendance records and instructor’s teaching evaluation scores are analyzed. The results show that students were strongly positive with the use of Socrative and felt that they were more engaged. This interactive model has successfully enhanced students’ learning experience and improved students’ academic performance. The outcome of this study would contributes to current evidence of the efficacy of using mobile technology in higher education teaching.